Biomimetic Versatile Anisotropic, Electroactive Cellulose Hydrogel Scaffolds Tailored from Fern Stem Serving as Nerve Conduit and Cardiac Patch - Qinghui Liang; Shuhui Chen; Shaofeng Hua; Weihong Jiang; Jiamian Zhan; Chunyi Pu; Rurong Lin; Yutong He; Honghao Hou; Xiaozhong Qiu (Advanced Science)
Abstract Peripheral nerve injury (PNI) and myocardial infarction (MI) are the two most clinically common soft excitable tissue injuries. Both nerve and cardiac tissues exhibit structural anisotropy and electrophysiological activity, providing a wide range of biophysical cues for cell and tissue repair. However, balancing microstructural anisotropy, electroactivity, and biocompatibility is challenging. To address this issue, Dicranopteris linearis (D. linearis) is proposed as a low‐perceived value fern plant. Moreover, to enhance its usefulness, it can be designed into a tubular structure and a lamellar structure to bridge the damaged tissue. Therefore, a robust yet simple top‐down approach is proposed to designing and fabricating the desired biomimetic versatile hydrogels orienting from the D. linearis to customize for different soft excitable tissue repair applications. These anisotropic electroactive hydrogels performed well as nerve guidance conduits (NGC) and engineered cardiac patches (ECP) in the repair of PNI and MI, respectively. Two birds, one stone. Accordingly, the biomimetic strategy of D. linearis to NGC and D. linearis to ECP is first proposed, opening a new horizon for constructing tissue engineering using natural sources.